Enhancing Geo-Culinary Competitiveness of MSMEs through Sustainable Marketing in Geopark West Java Indonesia - Yuliawati , Ayu Krishna; Rofaida , Rofi; Gautama , Budhi Pamungkas; Wulung, Shandra Rama Panji; Millah , Riza Saepul; Aryanti , Asti Nur; Hadian , Mohamad Sapari Dwi (Journal of Ecohumanism, 2025)
This study investigates the sustainable marketing and competitiveness of geoculinary products in the geopark. The geopark in West Java Indonesia has geodiversity, biodiversity and culturediversity contribute unique characteristics to local culinary offerings, elevating their appeal in international markets. Geodiversity enhances the quality of raw materials; biodiversity ensures a sustainable supply of distinct ingredients, and cultural diversity enriches the processing and presentation, making these culinary products highly marketable. The results show sustainable marketing positively affected competitiveness through the mediation of innovation strategy in MSMEs (Micro Small Medium Enterprise). The study found sustainable marketing have influence on MSME’s competitiveness, through innovations. The MSMEs innovations, include culture-based storytelling, sustainable packaging, and certifications, all fostering trust and loyalty among global consumers. The findings demonstrate by combining traditional and digital marketing approaches, focusing on sustainability, culture, and technological innovation, significantly boosts the competitiveness of MSMEs in the geo-culinary sector. The study recommends capitalizing on geodiversity and biodiversity, adopting environmentally friendly production processes, and leveraging sustainable marketing to enhance global market competitiveness.